Do coaches perceive themselves as influential on physical activity for girls in organised youth sport? - Guagliano, Justin M.; Lonsdale, Chris; Rosenkranz, Richard R.; Kolt, Gregory S.; George, Emma S. (My University, 2014)
Participation in organised youth sports (OYS) has been recommended as an opportunity to increase young peoples’ physical activity (PA) levels. While coaches can potentially influence athletes’ PA levels, what has not been explored is the question; do coaches perceive themselves as influential on PA for girls in OYS? Participants were 30 coaches of girls OYS teams aged 9–17 years in the Greater Sydney Metropolitan Area, Australia. Participants took part in a semi-structured interview that lasted approximately 30 minutes. They responded to questions regarding their perceived role as coaches, their perceptions of themselves as role models for PA, their views on their athletes’ current PA levels, their opinions on improving their athletes’ PA levels, and their perceived challenges as coaches in OYS. Many coaches considered themselves role models for PA due to their own involvement in organised sports. Coaches felt that they were conscious of girls’ PA levels during training and could accurately gauge how active girls were. Coaches perceived their training sessions to provide sufficient PA and thus, did not feel the need to try to increase PA during training. Many coaches were cautious about conducting training sessions where the PA intensity was high for prolonged periods because they believed that it could potentially result in dropout from OYS. Coaches’ perceived time commitment to OYS, variability of skill/experience amongst girls, and poor parental support as major challenges they experienced in OYS. This study provided a unique insight from the perspective of coaches in OYS. Most coaches felt that they had the potential to influence PA for girls in OYS; however, coaches may underestimate or not fully realise the impact they can have on the girls they coach. Future research should focus on educating coaches to capitalise on the opportunity they have to promote PA through OYS.
Keywords: Adolescents; Behavioral and social aspects of health; Children; Exercise; Games; Health education and awareness; Physical fitness; Teachers